Avaliação do desenvolvimento de colônias de abelhas africanizadas (apis mellifera) e do ganho de peso como critério de seleção para produção de mel no semiárido - Trajano, André Luiz Machado (Universidade Federal Rural do Semi-Árido, 2020)
Brazilian beekeeping has not kept up with the productive pattern of some countries that have evolved more in honey production, even with the enormous beekeeping potential, including in the semiarid region. The long off-season and the short longevity of their queen bees are limiting factors for increasing productivity in the region. Beekeepers then need to adapt the management to improve production efficiency, by monitoring the number of offspring in the pre-harvest, so that there is a greater number of bees in the collection of nectar during the flowering period. The selection of bee colonies, based on the production of honey at the end of the harvest, allows to improve productivity with each generation of a new queen. However, the absence of drones right after the harvest period, makes it impossible to cross with unfertilized queens from the hives that produced more in that period. Therefore, early identification of colonies with superior performance can anticipate the preparation of selected queens, inducing their fertilization during the harvest and thus obtain improved generations. In addition, the behavior of Africanized bees in the semiarid region needs to be better studied. The objective of this work was to evaluate the development of colonies of Africanized bees (Apis mellifera) in the pre-harvest period and weight gain as a selection criterion for honey production during the harvest. 21 colonies were used, divided according to the number of frames with offspring: strong, intermediate and weak, with the replacement of the old queens in this last group at the beginning of the experiment. The works were divided into 2 periods: pre-harvest (January to April 2019) and harvest (May to July 2019), according to the availability of flowering. During the harvest, weight gain was recorded in four intervals. It was observed in the development of weak colonies, that after the replacement of queens, they approached the intermediate and strong, in number of frames with offspring, demonstrating that the replacement of queens in the pre-harvest can improve productivity. The results of weight gain showed that the first two intervals (beginning of the harvest) showed high correlations (0.89 and 0.87, respectively) and significant (P <0.001) between weight gain and honey production, indicating this criterion at the beginning of the harvest to make the selection early. These results are promising, as they suggest that in this period new queens can be produced and fertilized even during the harvest, from the selected matrices, forming a bank of improved queens. These queens could be used to: a) replace old queens that are showing, during the harvest, inadequate posture or low honey production; b) replace all queens at the end of the season; c) be commercialized or even maintained to produce new colonies, contributing to the increase in honey productivity in the semiarid region
Keywords: Apicultura; Manejo; Melhoramento; Pré-safra; Safra; Produtividade; Beekeeping; Management; Pre-harvest; Harvest; Productivity; CIENCIAS AGRARIAS::ZOOTECNIA::PRODUCAO ANIMAL